Behavioral phenotyping of Kaiso-deficient mice - V. S. Korostina; A. V. Kulikov (Вавиловский журнал генетики и селекции, 2015)
Kaiso is a methyl DNA-binding protein, which participates in the epigenetic regulation of gene expression. It binds methylated DNA with its zinc-finger domain and recruits repressive protein complexes to the methylated DNA fragments by the interaction of the BTB/POZ domain with the complex of NCoR corepressor and histone deacetylase, thereby performing transcription repression. A Kaiso-deficient mouse strain (KO) with the C57BL/6 strain background has been bred. Here we compare the behavior of KO mice and wild-type control C57BL/6 mice (WT) in the classic battery of behavioral tests, including the open field, elevated plus maze, and forced swim tests. We have shown that knockout of the Kaiso gene increases the locomotory and exploratory activities of KO mice in the open field test. Kaiso-deficient mice spend more time in the center of the open field than WT mice. No effect of Kaiso gene knockout on anxietyrelated behavior has been observed in the elevated plus-maze. However, Kaiso gene deficiency produces a pronounced antidepressant-like effect in the forced swim test: Unlike WT mice, KO mice do not show any depressive-like freezing in this test. These results are the first piece of experimental evidence for the involvement of Kaiso protein in the regulation of brain functioning and behavior. The Kaiso-deficient strain is a new and promising model of the genetic, molecular, and neuronal mechanisms mediating the epigenetic regulation of brain functions and behavior.